Unique high-temperature performance of highly condensed MnBi permanent magnets. (October 2015) - Chen, Yu-Chun; Gregori, Giuliano; Leineweber, Andreas; Qu, Fei; Chen, Chia-Chin; Tietze, Thomas; Kronmüller, Helmut; Schütz, Gisela; Goering, Eberhard
Abstract : High-performance MnBi isotropic magnets have been prepared via spark-plasma-sintering, which achieves bulk magnets with high densification and little grain growth. The sintered magnets in this work show high saturation magnetization at high temperatures. Moreover, hard magnetic behavior is still present after heating beyond its phase transition temperature. The exceptional thermal stability could be due to the observed fine-grained microstructure. The analysis of temperature dependence of coercivity behavior demonstrates that the magnetization process can be explained by nucleation model.